Formula Organik Cair Berbahan Tikus Sawah Di Desa Kandangan Kecamatan Cerme Gresik - Nur Hafif; Ramadan Saputra; Ego Lion Sakty; Faisol Humaidi4 (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service is to change the function of rat pests into organic fertilizer products. In this service, the method used is descriptive qualitative. The technique of determining the informants was done by purposive sampling, data collection techniques were observation, in-depth interviews, and documents. The analysis of the data used is qualitative, it can obtain regularity and systematic, the three of which are interrelated, namely: data reduction, data presentation, drawing conclusions. The results of the processing of organic fertilizers do not use sophisticated equipment but only use manual equipment made with special assemblies with ordinary tools, the first process carried out is arresting, then killing, weighing, soaking, draining and using them at the time of processing. rice field irrigation.